Eighteen years of Clearfield™ rice in Brazil: what have we learned?. Issue 5 (30th September 2021) - Avila, Luis Antonio de; Marchesan, Enio; Camargo, Edinalvo R.; Merotto, Aldo; Ulguim, André da Rosa; Noldin, José Alberto; Andres, André; Mariot, Carlos H. P.; Agostinetto, Dirceu; Dornelles, Sylvio H. B.; Markus, Catarine
Abstract: Clearfield™ (CL) rice ( Oryza sativa L.) is a weedy rice ( Oryza spp.; synonym = red rice) control tool that has been used in Brazil since 2003. This system includes the use of an imidazolinone (IMI)-tolerant cultivar and the application of IMI herbicides. In this review article, Brazilian weed scientists evaluate the challenges and lessons learned over 18 yr of CL use. CL system benefits include selective weedy rice control, better crop establishment during the most advantageous period of the year, and more efficient fertilizer use. In Rio Grande do Sul state, the CL system, in conjunction with other improvements, has contributed to rice grain yield gains from 5, 500 kg ha −1 before 2002 to around 8, 400 kg ha −1 currently. In contrast, the main problem that has arisen over this period is the rapid evolution of IMI-resistant weedy rice, caused by gene flow from CL rice cultivars. The off-label use (rate and continuous use) of IMI herbicides has contributed to the evolution of resistance in Echinochloa spp. and other weeds. IMI herbicide carryover has also affected susceptible crops grown after CL rice. Crop rotation with soybean [ Glycine max (L.) Merr.] is increasing, ensuring system sustainability. The importance of minimum tillage has also become apparent. Such cultivation includes applying nonselective herbicides before sowing or just before crop emergence (at the spiking stage to eliminate as much weedy rice as possible and other weeds at an early growth stage). It also includes the use of certified seeds free of weedy rice, following label instructions for IMI herbicides, applying the herbicide PRE followed by POST, and complementary weedy rice management practices, such as roguing of surviving weedy rice plants.